2016
DOI: 10.1242/jeb.150540
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fertility and chill tolerance after cold-induced reproductive arrest in females of temperate species of the Drosophila buzzatii complex

Abstract: Long-term exposure to low temperatures during adult maturation might decrease fertility after cold recovery as a consequence of carryover effects on reproductive tissues. This pattern should be more pronounced in tropical than in temperate species as protective mechanisms against chilling injuries are expected to be more effective in the latter. We initially determined the lower thermal thresholds to induce ovarian maturation in four closely related Drosophila species, two inhabiting temperate regions and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Expression of chorion-related genes follows this pattern as highest expression has been reported at intermediate temperatures [49]. The lowest developmental thermal threshold for ovarian maturation is generally around 10–12 °C in temperate drosophilids [99]. In D. suzukii , studies reported a reproductive dormancy mainly due to development at low temperature [33, 34, 37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of chorion-related genes follows this pattern as highest expression has been reported at intermediate temperatures [49]. The lowest developmental thermal threshold for ovarian maturation is generally around 10–12 °C in temperate drosophilids [99]. In D. suzukii , studies reported a reproductive dormancy mainly due to development at low temperature [33, 34, 37].…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether arrest of oogenesis is a passive consequence of low temperature with no adaptive value for cold tolerance or whether this mechanism is an active protective strategy. Data from drosophila species support that cold-induced oogenesis arrest (via quiescence or diapause) is actually part of an integrated mechanism of cold adaptation and cold stress tolerance mechanism [99, 101].…”
Section: Discussionmentioning
confidence: 99%
“…It results that temperate populations are usually better able to cope with low temperature stress than their tropical counterparts, as reported in flesh flies for instance (Chen et al, 1990). Likewise, Drosophila species from tropical origins are often much less cold tolerant than species found in temperate areas (Gibert et al, 2001;Goto and Kimura, 1998;Kellermann et al, 2012;Mensch et al, 2017;Olsson et al, 2016). However, whether species adapted to tropical climates are capable of tolerating cold stress, and by which physiological mechanisms they can do so, remains a poorly explored question.…”
Section: Introductionmentioning
confidence: 99%
“…Figure S1 shows the phylogenetic relationships of species under studied. While D. venezolana and D. borborema are inhabitants of tropical deserts where environmental temperatures are warm and mostly uniform throughout the year, D. koepferae and D. buzzatii can reach areas of higher latitudes or altitudes in subtropical and temperate regions, where cold seasons likely challenges survival and fertility (Mensch et al, 2017). Climatic data from locations where the species were collected indicate that tropical and temperate species are exposed to very distinct conditions in nature (Figure S2).…”
Section: Introductionmentioning
confidence: 99%